Histories of substance use and risk behavior: precursors to HIV seroconversion in homosexual men. - Chesney, M A (1998)
OBJECTIVES: This study compared history of substance use and episodic use in terms of HIV seroconversion. METHODS: A sample of 337 baseline HIV-negative gay men was followed for 6 years. Bivariate and survival analyses were used to compare 39 converters with nonconverters on substance use behaviors. RESULTS: Seroconverters were consistently more likely to report use of marijuana, nitrite inhalants, amphetamines, and cocaine than nonconverters. Consistent use of nitrite inhalants and amphetamines increases the relative risk of seroconversion, while episodic use does not. Both patterns of cocaine use increase seroconversion risk. CONCLUSIONS: There are three potential mechanisms for an increased risk of conversion due to consistent substance use.